Operation of the Microgrid with Improved Droop Control Strategy and an Effective Islanding Detection Technique for Automatic Mode Switching. Issue 4 (3rd November 2021) - Kulkarni, Shreeram V; Gaonkar, Dattatraya N; Guerrero, Josep M
Abstract: This paper presents the islanding detection and automatic mode switching for inverter-based distributed generation sources (DGs) in the microgrid with an improved droop controlled scheme. The modification in the conventional droop among the DGs is contrived to share the load proportionate to their power capacity. And to reduce the circulating currents and to improve reactive power-sharing the virtual impedance is implemented for the microgrid in the stand-alone mode operation. Also, the modified Park synchronous reference frame based phase-locked loop (PSRF-PLL) is implemented for the operation of the microgrid in the grid-connected mode. The islanding detection and automatic mode switching depend on the PSRF-PLL, which uses the input obtained from the stationary reference frame. The proposed PLL implemented in this work is simple in construction and keeps the phase locking error to near zero, thus leading to proper locking with reduced complexity. The control scheme's performance in the microgrid is validated using the real time hardware in the loop platform. The performance of PSRF-PLL based islanding detection scheme is analyzed considering the various grid disturbances, and the comparative study with the other PLL based scheme is also presented in this paper to show the improved performance of the proposed PSRF-PLL scheme.